2005
DOI: 10.1510/icvts.2004.093229
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted cardioscopy in a patient with left ventricular tumor of unknown etiology

Abstract: Ventricular tumors are a rare clinical entity with limited possibilities for excision diagnosis. For benign conditions surgical excision is the treatment of choice. A case presenting as a clinical conundrum with left ventricular tumor and complex past medical history is discussed. Aortic transvalvular video-assisted cardioscopy was used for removal and definitive diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35]. Other adjunct endoscopic instruments such as forceps, graspers, scissors, suckers or retractors were used in 13 studies [2, 3, 12, 13, 15, 19, 21, 25, 30, 32, 34, 35, 37]. In the remaining it was not clear whether open surgical or endoscopic instruments were used.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In 13 studies, the type of endoscope used was not specified [4, 6, 10, 15, 20, 2428, 31, 34, 35]. Other adjunct endoscopic instruments such as forceps, graspers, scissors, suckers or retractors were used in 13 studies [2, 3, 12, 13, 15, 19, 21, 25, 30, 32, 34, 35, 37]. In the remaining it was not clear whether open surgical or endoscopic instruments were used.…”
Section: Resultsmentioning
confidence: 99%
“…There were no mortalities (0/47) among 27 studies at last recorded follow-up (Table 2) [213, 15, 19, 2128, 3135]. In 12 studies, the follow-up was longer than 30-days and no mortalities were observed [2, 3, 5, 6, 8, 9, 12, 25, 26, 31, 33, 35].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations